Answer:
x=-28
Step-by-step explanation:
you multiply the number first
and you calculate
then you move constant to the right
you changes the sign
done!
We can get two different equations from this:
3x = 18
and
3x = -18
So:
x = 6, x = -6
x = {6, -6}
First u do a squared +b squared =c squared aka pythagorean theorem then so u already have c squared so you would do 5x5=25 and 13x13=169 so then the equation would be 25+?=169 then do 169-25 which equals 144 and then do the square root of that which is 12 THE ANSWER IS 12
Answer:
yes
Step-by-step explanation:
Because all the numbers are the same